PENGARUH e-WOM DAN CITRA DESTINASI TERHADAP NIAT BERKUNJUNG KEMBALI KE PANTAI SENGGIGI DI TENGAH WABAH COVID-19 - Lalu Adi Permadi; Layla Vidatul Ula; Dwi Putra Buana Sakti (Master of Management, Mataram University, 2020)
This study aims to determine the effect of the Electronic Word of Mouth variable and destination image on the interest of tourists visiting Senggigi beach. This type of research is an associative research with a quantitative approach. The population in this study is archipelago tourists who have visited Senggigi beach with a total sample of 100 respondents. The analysis showed that the Electronic Word of Mouth variable (EWOM) influenced the interest of tourists visiting Senggigi Beach and the destination image variable influenced the interest of tourists visiting Senggigi Beach.Keywords:Electronic Word of Mouth (EWOM), Destination Image, Revisiting Interest.